2015
DOI: 10.1016/j.jbiotec.2014.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Engineering β1,4-galactosyltransferase I to reduce secretion and enhance N-glycan elongation in insect cells

Abstract: β1,4-galactosyltransferase (B4GALT1) is a Golgi-resident enzyme that elongates glycoprotein glycans, but a subpopulation of this enzyme is secreted following proteolytic cleavage in its stem domain. We hypothesized that engineering B4GALT1 to block cleavage and secretion would enhance its retention and, therefore, its function. To test this hypothesis, we replaced the cytoplasmic/transmembrane/stem (CTS) domains of B4GALT1 with those from human α1,3-fucosyltransferase 7 (FUT7), which is not cleaved and secrete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 79 publications
(136 reference statements)
0
18
0
Order By: Relevance
“…Fifty mL shake flask cultures of Sf-RVN and Sf9 cells were infected with Sf-rhabdovirus-negative stocks of AcP(−)p6.9hEPO and hEPO was affinity purified from the cell- and virus-free supernatants using Ni-NTA resin (ThermoFisher), as described previously [23]. N -glycans were enzymatically released from the purified hEPO preparations by digestion with PNGaseF (New England Biolabs), and the released N -glycans were purified, derivatized, and analyzed by MALDI-TOF-MS as described previously [23].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fifty mL shake flask cultures of Sf-RVN and Sf9 cells were infected with Sf-rhabdovirus-negative stocks of AcP(−)p6.9hEPO and hEPO was affinity purified from the cell- and virus-free supernatants using Ni-NTA resin (ThermoFisher), as described previously [23]. N -glycans were enzymatically released from the purified hEPO preparations by digestion with PNGaseF (New England Biolabs), and the released N -glycans were purified, derivatized, and analyzed by MALDI-TOF-MS as described previously [23].…”
Section: Methodsmentioning
confidence: 99%
“…N -glycans were enzymatically released from the purified hEPO preparations by digestion with PNGaseF (New England Biolabs), and the released N -glycans were purified, derivatized, and analyzed by MALDI-TOF-MS as described previously [23]. Structures were assigned to peaks based on predicted masses and knowledge of the N -glycans produced in Sf cells.…”
Section: Methodsmentioning
confidence: 99%
“…typhimurium (Manuel et al 2011), S. lividans (Dubeau et al 2009), wheat (Mihálik et al 2015), transplastomic tobacco plants (chloroplast translation system) (Occhialini et al 2015), P. berghei (Singer et al 2015), S. frugiperda (Geisler et al 2015), S. pneumoniae (Overkamp et al 2013), A.…”
Section: Acc E P Ted P R E P R I Ntmentioning
confidence: 99%
“…Many of the codon optimization software lack citations. Of these software packages, citations have been found for JCat and OPTIMIZER for expression systems such as E. coli (Fahimi et al, 2016;Guo et al, 2016;Karkhah and Amani, 2016;Zhao et al, 2016), S. cerevisiae (Ask et al, 2013;Guadalupe-Medina et al, 2013;Li et al, 2015;Milne et al, 2015;Solis-Escalante et al, 2013), N. benthamiana (Binder et al, 2014), HEK293 cells (Shah et al, 2015), B. subtilis (Reilman et al, 2014), Caulobacter crescentus (Ko et al, 2013), Pseudomonas putida (Dammeyer et al, 2011(Dammeyer et al, , 2013, Salmonella typhimurium (Manuel et al, 2011), S. lividans (Dubeau et al, 2009), wheat (Mih alik et al, 2015, transplastomic tobacco plants (chloroplast translation system) (Occhialini et al, 2015), Plasmodium berghei (Singer et al, 2015), Spodoptera frugiperda (Geisler et al, 2015), S. pneumoniae (Overkamp et al, 2013), A. marginale (Pierl e et al, 2013), R. pomeroyi (Green et al, 2013), L. acidophilus (Askelson et al, 2014), C. reinhardtir (Erpel et al, 2016), Y. lipolytica (Matthaus et al, 2014), S. elongates (van der Woude et al, 2016), and baculovirus (Maghodia et al, 2016). While it is encouraging that codon optimization software programs are used for a variety of species and purposes, most of the papers do not compare yields of native and codon optimized sequences, so yield comparisons cannot be made.…”
Section: Development Of Algorithms For Synthetic Genesmentioning
confidence: 99%
“…We can potentially attribute a reduction in bigalactosylated and biantennary‐glycans following the removal of core fucose and sialyltransferase to a possible change in the interaction between galactosyltransferase or other transferases and certain mutant IgGs with specific amino acid mutations (F241A and F243A). Interestingly, Geisler, Mabashi‐Asazuma, Kuo, Khoo, & Jarvis () reported that overexpression of B4GALT1 can increase galactosylation but also decrease the core fucosylation, which suggests a competition or inhibition of fucosyltransferase following elevation of the galactosyltransferase activity.…”
Section: Discussionmentioning
confidence: 99%